Comprehensive analysis of the PRPF31 gene in retinitis pigmentosa patients: Four novel Alu‐mediated copy number variations at the PRPF31 locus. Issue 12 (9th November 2022) - Chen, Zhixuan; Chen, Jieqiong; Gao, Min; Liu, Yang; Wu, Yidong; Wang, Yafang; Gong, Yuanyuan; Yu, Suqin; Liu, Wenjia; Wan, Xiaoling; Sun, Xiaodong
Abstract: Retinitis pigmentosa (RP) is a monogenic disease characterized by irreversible degeneration of the retina. PRPF31, the second most common causative gene of autosomal dominant RP, frequently harbors copy number variations (CNVs), but the underlying mechanism is unclear. In this study, we summarized the phenotypic and genotypic characteristics of 18 RP families (F01−F18) with variants in PRPF31 . The prevalence of PRPF31 variants in our cohort of Chinese RP families was 1.7% (18/1024). Seventeen different variants in PRPF31 were detected, including eight novel variants. Notably, four novel CNVs encompassing PRPF31, with a proportion of 22.2% (4/18), were validated to harbor gross deletions involving Alu / Alu ‐mediated rearrangements (AAMRs) in the same orientation. Among a total of 12 CNVs of PRPF31 with breakpoints mapped on nucleotide‐resolution, 10 variants (83.3%) were presumably mediated by Alu elements. Furthermore, we described the correlation between the genotypes and phenotypes in PRPF31 ‐related RP. Our findings expand the mutational spectrum of the PRPF31 gene and provide strong evidence that Alu elements of PRPF31 probably contribute to the susceptibility to genomic rearrangement in this locus.